The Influence Of Discount And Promotion Programs On Alfamart Consumers' Purchase Decisions General Sudirman Manna South Bengkulu - Selsa Dlayorza; Monique, Eska Prima; Hidayah, Nenden Restu (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
This study employed an associative survey method with a quantitative approach. The sample consisted of 171 Alfamart consumers, using a purposive sampling technique. Data collection used a questionnaire. Quantitative data analysis was conducted using multiple linear regression analysis and hypothesis testing, consisting of t-tests and F-tests. The results showed that discount programs influenced purchasing decisions among consumers at Alfamart, Jalan Jenderal Sudirman, Manna, South Bengkulu, with a calculated t value > t table (3.441 > 1.65403) and a significance level of 0.001 < 0.050. Promotions influence purchasing decisions among Alfamart consumers on Jalan Jenderal Sudirman Manna, South Bengkulu, with a calculated t value > t table (5.110 > 1.65403) and (sig a = 0.000 < 0.050). Discount programs and promotions simultaneously influence purchasing decisions (Y) among Alfamart consumers on Jalan Jenderal Sudirman Manna, South Bengkulu, with an F value of 31.787 > 3.05 and a significance value of 0.000 < 0.05.